History and the Climate Crisis - hawkey, kate (Knowledge and the Curriculum, 2023)
History education has a key contribution to make in developing a deeper understanding of the current environmental crisis, but its role is too often overlooked. When embedded in the school curriculum, environmental history adds crucial layers of knowledge to the learning from other subjects and can enable students to make their own informed contributions to one of the most pressing concerns of the 21st century. History and the Climate Crisis makes the case for including an environmental focus in the secondary school history curriculum by locating its arguments within established historiographical and revisionist debates. It provides much-needed subject knowledge in an area that is new for most history teachers. The author considers the disciplinary and pedagogical challenges and demonstrates how including an environmental focus can strengthen students' disciplinary knowledge. She also builds her argument through the use of many examples and offers practical strategies for use in classrooms, including developed enquiries suitable for the secondary history curriculum. The book focuses on environmental history within a strong subject bound curriculum and will be relevant to teachers, academics and policymakers in the UK and internationally. Praise for History and the Climate Crisis 'There has never been a better time to explore how history can help young people make sense of the climate crisis and this book is the perfect starting point. It takes us on a journey across broad timespans and smaller stories, providing fresh insights into what is already taught in classrooms and introducing us to surprising and fascinating perspectives along the way. Its breadth and accessibility will make it indispensable to teachers at every stage of their career and I cannot recommend it highly enough.' Dr Alison Kitson, Associate Professor of Education and Programme Director, Centre for Climate Change and Sustainability Education, UCL Institute of Education 'A welcome and much-needed book that will be invaluable for all those thinking about how to better integrate environmental sciences and history into the classroom. An incredibly helpful resource for teachers - and therefore for pupils too.' Peter Frankopan, Professor of Global History, Worcester College, University of Oxford